BIAS TEOLOGIS DALAM LINGUISTIK ARAB (?) (Telaah atas Prinsip ’Āmil dan Ta’līl dalam Nahwu) Oleh: Zamzam Afandi - Zamzam Afandi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
This paper aims at describing and analyzing the mostimportant principles in nahwu, that are ‘āmil and ‘illah or ta’līl, not from how they work but from how they function, which is from the theological perspective. The main reason for this is because generally the linguists, who are involved intensively in the study of nahwu, belong to various theological mainstreams, for example Mu’tazilah and Asy’ariyah. By elaborating the critical method of theology, it is expected that the case of ‘āmil and ‘illah or ta’līl are more comprehensible.